2003
DOI: 10.1002/zaac.200300029
|View full text |Cite
|
Sign up to set email alerts
|

The Successive Fragmentation of a Structurally Characterized Metalloid Cluster Anion in the Gas Phase: [Ga13(GaR)6] → ··· → [Ga13] + 6 GaR (R = C(SiMe3)3)

Abstract: By collisions with argon atoms in the gas phase (SORI‐CAD experiments by means of FT‐ICR mass spectrometry) the metalloid cluster ion [Ga19(C(SiMe3)3)6]— fragments in a very precise way detaching step by step neutral Ga(C(SiMe3)3) units and finally leading to the stable 40‐electron bare metal cluster [Ga13]—. In combination with quantum chemical calculations the exploration of the fragmentation process leads to an experimentally based understanding of the bond properties of many of the recently investigated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 50 publications
0
16
0
4
Order By: Relevance
“…[20,21,26] In addition, Schnöckel et al, reported generation of bare Ga 13 − by fragmentation of structurally characterized clusters such as [Ga 13 (GaC(SiMe 3 ) 3 ) 6 ] -. [12,13,27] Although these approaches are sophisticated and allow variations in the clusters possible by changing the type of protecting ligands or synthesis conditions, they are basically thermodynamic syntheses. Therefore, the obtained clusters are strongly affected by their thermodynamic stability.…”
Section: Doi: 101002/adma201907167mentioning
confidence: 99%
See 1 more Smart Citation
“…[20,21,26] In addition, Schnöckel et al, reported generation of bare Ga 13 − by fragmentation of structurally characterized clusters such as [Ga 13 (GaC(SiMe 3 ) 3 ) 6 ] -. [12,13,27] Although these approaches are sophisticated and allow variations in the clusters possible by changing the type of protecting ligands or synthesis conditions, they are basically thermodynamic syntheses. Therefore, the obtained clusters are strongly affected by their thermodynamic stability.…”
Section: Doi: 101002/adma201907167mentioning
confidence: 99%
“…Therefore, the obtained clusters are strongly affected by their thermodynamic stability. [28] In this study, we demonstrate control of the valence electrons in superatomic gallium clusters [26,27,29,30] using our superatom synthesizer, that is, fourth generation dendritic polyphenylazomethines (DPAs). [31] Gallium is known to have a low melting point compared to other metals in the bulk state.…”
Section: Doi: 101002/adma201907167mentioning
confidence: 99%
“…Its solubility gave us the possibility of detecting a mass spectrum of this cluster using ESI (electrospray ionization) as the ionization method. The results of this revealed that it is possible to transfer this metalloid cluster into the gas phase without fragmentation [13]. The dissociation experiments (SORI-CAD= sustained off-resonance irradiation-collision-activated dissociation) showed that the metalloid cluster [Ga 19 R 6 ] -(R=C(SiMe 3 ) 3 ) fragments in a precise way, detaching neutral GaR units.…”
Section: Resultsmentioning
confidence: 95%
“…In other words, this is the first time that the advantages of gas-phase investigations could be applied to a metalloid cluster the structure of which is known exactly. Together with quantum-chemical calculations the dissociation experiments revealed that the gallium atoms in the inner part of the metalloid cluster are, indeed, different from the other gallium atoms [13]. The characteristics of the "naked" gallium atoms are comparable with those of gallium atoms in bulk gallium metal whereas the outer gallium atoms, those bound to the organic ligands, are comparable with gallium atoms in organometallic gallium compounds.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation